AI for food systems transformation: CGIAR’s readiness, momentum, and investment opportunity - Jones-Garcia, Eliot; Martins, Carolina; Magalhaes, Marilia; Koo, Jawoo (CGIAR System Organization, 2025)
Artificial intelligence is reshaping scientific research, yet most institutions struggle to translate this potential into concrete value. The challenge is not technical; it stems from missing incentives, misaligned workflows and work culture, emotional and institutional frictions, etc. CGIAR faces similar dynamics: high expectations for AI, but uneven adoption and capacity across Centers, with limited alignment across the System. At the same time, CGIAR holds key advantages over other global research players. Decades of science, vast geospatial footprints and datasets, strong partnerships with governments and national partners, and a public-good mandate position CGIAR as a global leader in AI for food systems. With targeted investment, CGIAR can translate this advantage into acceleration of science, stronger country delivery, and new digital public goods that shape global food policy and innovation.